Perspective Transformation Over Time: A Two-year Follow-up Study of HIV-Positive Adults - Bradley C. Courtenay; Sharan B. Merriam; Patricia M. Reeves; Lisa M. Baumgartner (Adult Education Research Conference, 1999)
This study investigated the stability of a perspective transformation over time. The findings confirmed that perspective transformations, at least in our sample, are irreversible; we also discovered that meaning schemes continue to change.